1992
DOI: 10.1007/bf00602357
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbohydrate feedings on plasma free tryptophan and branched-chain amino acids during prolonged cycling

Abstract: Brain serotonin (5-hydroxytryptamine, 5-HT) has been suggested to be involved in central fatigue during prolonged exercise. Changes in the ratio of plasma free tryptophan (free Trp) to branched-chain amino acids (BCAA) are associated with altered brain 5-HT synthesis. The purposes of this study were to describe systematically the effects of prolonged exercise on changes in plasma free Trp and BCAA and to examine the effects of carbohydrate (CHO) feedings on these same variables. Eight well-trained men [VO2max … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
108
1
10

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(134 citation statements)
references
References 30 publications
15
108
1
10
Order By: Relevance
“…It has been reported that leptin production is not changed by short-term exercise (12,30). We can suggest that our observation in this study is similar, because no changes in leptin were seen during shortterm exercise.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…It has been reported that leptin production is not changed by short-term exercise (12,30). We can suggest that our observation in this study is similar, because no changes in leptin were seen during shortterm exercise.…”
Section: Discussionsupporting
confidence: 85%
“…The brain may detect changes in the normal levels of the constituents of the blood, such as the concentration ratio of tryptophan to branched-chain amino acids (4,6,7,11,12,(26)(27)(28)(29), which can then act as a specific signal to increase the organism's sensitivity to fatigue. However, little is known about the counteractive effects of the central nervous system (CNS) on peripheral energy metabolism.…”
mentioning
confidence: 99%
“…Central fatigue is aggravated by hyperthermia (47,48), but the neurobiological mechanism(s) underlying this type of fatigue is unknown. Special attention has been given to the synthesis and metabolism of serotonin (5-hydroxytryptamine), because of its role in arousal, sleepiness, and mood (5,13,15,42,51). Cerebral serotonin kinetics cannot be assessed directly in humans, because its passage across the blood-brain barrier is limited (27).…”
mentioning
confidence: 99%
“…Because carbohydrate ingestion has also been shown to reduce the availability of free tryptophan and to improve endurance for prolonged exercise (18), we also determined whether combined tyrosine and carbohydrate supplementation has a greater beneficial effect on endurance than either one alone.…”
mentioning
confidence: 99%